Effect of Disease-Modifying Therapy on Disability in Relapsing-Remitting Multiple Sclerosis Over 15 Years. (2nd February 2021) - Kalincik, Tomas; Diouf, Ibrahima; Sharmin, Sifat; Malpas, Charles; Spelman, Tim; Horakova, Dana; Havrdova, Eva Kubala; Trojano, Maria; Izquierdo, Guillermo; Lugaresi, Alessandra; Prat, Alexandre; Girard, Marc; et al.
Abstract : Objective: To test the hypothesis that immunotherapy prevents long-term disability in relapsing-remitting multiple sclerosis (MS), we modeled disability outcomes in 14, 717 patients. Methods: We studied patients from MSBase followed for ≥1 year, with ≥3 visits, ≥1 visit per year, and exposed to MS therapy, and a subset of patients with ≥15-year follow-up. Marginal structural models were used to compare the cumulative hazards of 12-month confirmed increase and decrease in disability, Expanded Disability Status Scale (EDSS) step 6, and the incidence of relapses between treated and untreated periods. Marginal structural models were continuously readjusted for patient age, sex, pregnancy, date, disease course, time from first symptom, prior relapse history, disability, and MRI activity. Results: A total of 14, 717 patients were studied. During the treated periods, patients were less likely to experience relapses (hazard ratio 0.60, 95% confidence interval [CI] 0.43–0.82, p = 0.0016), worsening of disability (0.56, 0.38–0.82, p = 0.0026), and progress to EDSS step 6 (0.33, 0.19–0.59, p = 0.00019). Among 1, 085 patients with ≥15-year follow-up, the treated patients were less likely to experience relapses (0.59, 0.50–0.70, p = 10 −9 ) and worsening of disability (0.81, 0.67–0.99, p = 0.043). Conclusion: Continued treatment with MS immunotherapies reduces disability accrual by 19%–44% (95% CI 1%–62%), the risk of need of a walking aid by 67% (95% CI 41%–81%), and the frequency of relapses by 40–41% (95% CI 18%–57%) over 15 years. This study provides evidence that disease-modifying therapies are effective in improving disability outcomes in relapsing-remitting MS over the long term. Classification of Evidence: This study provides Class IV evidence that, for patients with relapsing-remitting MS, long-term exposure to immunotherapy prevents neurologic disability.